Plant Habitat Study of QaraDagh- Darbandikhan Area - Ahmad, Saman Abdulrahman; Ahmad, Nariman Salih; Salih, Sarbagh; Raza, Hana Ahmad; Ararat, Korsh (Sulaimani Journal for Pure and Applied Sciences, 2018)
A study was conducted on the plant habitat structure and the endemic species of QaraDagh-Darbandikhan area. The distribution of vegetation composition in both locations was identified. All vegetation zones and their keystone species are described in this manuscript. Historical data was integrated within the current records based on software applications. A habitat map was created, based on the topographical distribution of the study site. A total of 380 plant species belonging to 65 families were recorded. Within this total number, 44 taxa were identified as endemic species distributed with their occurrence in both QaraDagh and Darbandikhan areas. The current habitat is also important for different threatened fauna, especially the Persian Leopard (Panthera pardus saxicolor) and Wild Goat (Capra aegagrus) which according to IUCN Red List are Endangered and Vulnerable, respectively. Threatson the habitat assessed were overgrazing, random fires, road constructions/expansion, sign of urbanization expansion and pollution from the associated garbage and waste. In other locations, there are issues of agricultural expansion, reforestation of slopes by non-native trees and conversion of the natural habitat to vineyards and orchards, using different species of forest communities as firewood. The result of this study confirms the urgent need for plant habitat conservation in the study area for the sustainability of the living communities
Keywords: Plant habitat; biodiversity; endemic species; vegetation zone; Persian leopard; conservation